Surface‐Driven Evolution of the Anomalous Hall Effect in Magnetic Topological Insulator MnBi2Te4 Thin Films. (26th May 2022) - Mazza, Alessandro R.; Lapano, Jason; MeyerIII, Harry M.; Nelson, Christopher T.; Smith, Tyler; Pai, Yun‐Yi; Noordhoek, Kyle; Lawrie, Benjamin J.; Charlton, Timothy R.; Moore, Robert G.; Ward, T. Zac; Du, Mao‐Hua; et al.
Abstract: Understanding the effects of the interfacial modification to the functional properties of magnetic topological insulator thin films is crucial for developing novel technological applications from spintronics to quantum computing. Here, a large electronic and magnetic response is reported to be induced in the intrinsic magnetic topological insulator MnBi2 Te4 by controlling the propagation of surface oxidation. It is shown that the formation of the surface oxide layer is confined to the top 1–2 unit cells but drives large changes in the overall magnetic response. Specifically, a dramatic reversal of the sign of the anomalous Hall effect is observed to be driven by finite thickness magnetism, which indicates that the film splits into distinct magnetic layers each with a unique electronic signature. These data reveal a delicate dependence of the overall magnetic and electronic response of MnBi2 Te4 on the stoichiometry of the top layers. This study suggests that perturbations resulting from surface oxidation may play a non‐trivial role in the stabilization of the quantum anomalous Hall effect in this system and that understanding targeted modifications to the surface may open new routes for engineering novel topological and magnetic responses in this fascinating material. Abstract : The electronic and magnetic response of the magnetic topological insulator MnBi2 Te4 is shown to be controllable by manipulating the surface chemistry in epitaxial thin films. This results in a dramatic reversal of the sign of the anomalous Hall effect driven by a change in the effective film thickness due to the non‐compensated magnetic moment.